In vitro Micropropagation of Bergenia ligulata (Hook. f. & Thomson) Engl. through Leaf Explant - Rani, S.; Puri, R.; Qasim, A.; Boora, P.; Angmo, D. (Journal of Scientific Research, 2023)
Berginia ligulata is medicinally significant and endangered plant of the western Himalayan Region. This plant is used to treat many diseases such as urinary problems and heart problems. By using leaf explant, an efficient and rapid micropropagation protocol was developed. In in-vitro propagation, MS medium was supplemented with benzyl amino purine (BAP), 1-naphthalene acetic acid (NAA) and indol-3-acetic acid (IAA) to induce multiple shoots from leaf explants. The most positive response for the formation of calluses was observed on MS media supplemented with MS medium + BAP(1 mg/L) + NAA(1 mg/L) followed by MS medium + BAP (0.5 mg/L) + NAA (1 mg/L) after 3 weeks. Maximum number of shoots were obtained on MS medium + BAP (2 mg/L) +IAA (2 mg/L). Maximum % shoot response was obtained on MS medium + Kn (2.5 mg/L) concentration. The maximum number of roots was observed on MS medium without growth regulators. These well-rooted plants were established in pots and acclimatized in the lab and transferred to field conditions. This process is useful to produce endangered plants on large scale.